PEDAGOGICAL FUNDAMENTALS OF THE INNOVATIVE APPROACH TO EDUCATION IN THE DIGITAL WORLD - Shirinoy Ortykalikizi Yusupova (Web of Journals Publishing, 2023)
The article talks about the pedagogical foundations of an innovative approach to education in the digital world.
Keywords: digital pedagogy, education, quality, efficiency, coherence.